PENGARUH LITERASI KEUANGAN, POLA PENGELUARAN, PENGENDALIAN DIRI, SIKAP TERHADAP RISIKO, PERILAKU MENABUNG DAN SOSIALISASI KEUANGANKELUARGA TERHADAP KESADARAN BERINVESTASI (STUDI PADA KARYAWAN SEKTOR PERBANKAN PADA BANK SMBC INDONESIA DI JAKARTA BARAT) - Ani Nugrahani; Erric Wijaya (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to analyze the influence of financial literacy, spending patterns, self-control, risk attitude, saving behavior, and family financial socialization on investment awareness. The study focuses on employees in the banking sector, specifically at Bank SMBC Indonesia located in South Jakarta. Hypothesis testing was conducted using the Partial Least Squares (PLS) method with the SmartPLS 4.0 software. Data collection was carried out through a questionnaire distributed via Google Forms to gather responses from participants. The results of the study indicate that financial literacy has a positive and significant effect on investment awareness. Spending patterns also have a positive and significant effect on investment awareness. Self-control shows a positive but not significant effect on investment awareness. Risk attitude has a positive and significant effect on investment awareness. Saving behavior demonstrates a positive and significant effect on investment awareness, while family financial socialization exhibits a positive but not significant effect on investment awareness.